Decreased imports of the Tigris and Euphrates and their effects on agricultural production (The governorates of central and southern Iraq as a model) - Jabor, Enteza rJassem; Jassim, Shorouq Naeem (Al-Adab Journal, 2015)
with the approach Turkey of the completion of the rest of the units and the Southeastern Anatolia Project in the coming years will become Iraq’s water situation is very critical as a result of storing more than the first (40-50%) of water from the Euphrates River and (17.5 -34%) of the Tigris River, and this of course, will lead to the emergence of a large water deficit in Iraq, which will reflect negatively on the overall conditions of economic and social damage inflicted by heavy in the whole areas and particularly agricultural. Cares search area alluvial plain as a model to demonstrate the impact of the scarcity of water of the Tigris and Euphrates on agricultural production where it represents the breadbasket of Iraq, but (80%) of the area that is easy to suffer from varying degrees of salinity and water logging as a result of several factors, including climate change and poor administration also, and that the fact that main rivers in Iraq are from neighboring countries, this is a major threat to ensure access to water resources on an ongoing basis and this matter threatens agricultural production where and displays large areas where desertification and what the resulting environmental problems and economic and social, the demand for water for agricultural use in Iraq, the most important of aspects of other uses and may be the proportion of agricultural use high may reach (92%) than among other uses and may be due to the primitive methods of irrigation used where frequent Lost water and waste large and misuse, but in spite of that, the real danger facing the agricultural production and the rest of the water needs in Iraq is the lack of imports water to the Tigris and Euphrates. From the foregoing that there is a scarcity of clear water sources in Iraq, as the effects of projected future climate changes suggest the possibility for spin and wiggle my future clear in amounts of precipitation and temperature increase, which would make the aggravation of fragility in the sector, sources of fresh water, as the quantity and quality sources of fresh water available is within the limits of danger most of the area of ​​Iraq within the desert and there are lands located within the area receives water rain less than (150 mm per year) as a result, Iraq is one of the countries that rely too heavily on neighboring countries (Turkey, Syria and Iran) to provide sources of fresh water flowing into Iraq through the Tigris and Euphrates and Karun, I have come to search a set of conclusions, including: Led proceed with Turkey to establish its water projects ambitious on the Tigris and Euphrates to inflict damage on Iraq, the problem faced by Iraq and the real tragedy caused by dams and reservoirs created by Turkey on the Tigris and Euphrates and non-observance of the rights of the lower reaches of the two rivers, which have affected the share Iraq’s water, which is very large impact on agricultural crops and turning the territory of Mesopotamia to the area suffers from scarcity of water needed by agriculture and other requirements, which predicts a veritable disaster exposed to Iraq not sanctioned by international law and the principles of Islam and the principles of neighborliness that links Turkey, and will continue water scarcity is increasing in the future as a result of increasing population and increasing per capita consumption of water and especially with the growing problem of drought in Iraq after the conversion of Iran to streams rivers and the establishment of Turkey for the dams on the Tigris and Euphrates and change weather and climate, and Iraq is exposed to sandstorms repeatedly and changing weather and dry the marshes and lakes and reservoirs and the encroachment of the desert on agricultural land, as well as offering large tracts of agricultural land in Iraq to drought and its transformation into a barren desert land with an estimated those spaces b (70%) of irrigated farmland in Iraq. Iran must not be excluded from deliberate harm her stay in Iraq through dams on tributary streams feeding the river Tigris rivers and the joint between the two countries and change some paths and withheld from access to Iraqi territory, causing great damage to the very farmlands and even the Iraqi marshes. The main recommendations are: The adoption of the principle of negotiation and dialogue with neighboring countries, including geographical rivers that flow to resolve the issues that relate to the use of water and distributed fairly among the riparian States and the conclusion of agreements in this regard to ensure the water quotas for these countries as determined by the norms and international laws. Adopting water policies that ensure the adequacy of use and reduce waste and conserve water pollution and counting water an essential component of any strategy for agricultural and activating the institutions of management and maintenance of irrigation and drainage on the Application of these policies and the development of systems and irrigation methods and distribution and the mechanics of re-water use and discharge and safe means of reducing wastage of them and store rain water and floods in surface reservoirs and groundwater, and the adoption of modern irrigation methods in agriculture and which do not consume large amounts of water, such as irrigation system, sprinkler or drip and others. .